Chill of fear - Hooper, Kay. (New York : Bantam Books, 2005)
Haunted by a twenty-year-old unsolved crime, FBI agent Quentin Hayes attempts to solve the myster and is joined by Diana Brisco, a woman struggling to unlock the meaning of her nightmares about a long-vanished child.
Keywords: Government investigators -- Fiction; Psychics -- Fiction; Tennessee -- Fiction; Romantic suspense fiction